Study of the influence of size effects in xSi3N4 - (1-x)ZrO2 ceramics obtained by solid-phase method on strength characteristics - Kenzhina И.Е.; Kozlovskiy А.Л.; Tolenova А.У. (Recent Contributions to Physics, 2024)
This research is focused on studying the influence of variation of component concentration of xSi3N4 - (1-x)ZrO2 type composite ceramics and conditions of mechanical-chemical grinding on the hardening of ceramics during their fabrication. As a result of the conducted research, the technology of obtaining composite ceramics of xSi3N4 - (1-x)ZrO2 type using the method of mechanical-chemical solid-phase synthesis was worked out. Obtaining ceramics was implemented using the method of mechanical activation of the initial components of silicon nitride and zirconium oxide, by mechanical grinding to achieve a homogeneous mixture, which was subsequently annealed in an oxygen-containing environment. In this case, the variation by different grain sizes, the change of which is associated not only with changes in the grinding conditions, but also the concentration of the ratio of the initial components. Using the methods of strength parameter estimation (indentation method), the influence of grinding conditions on the variation of dimensional factors, as well as the effectiveness of hardening was determined. Based on the conducted studies, it can be concluded that the use of mechanical-chemical solid-phase grinding by varying the speed of grinding (milling) leads to the control of dimensional effects in obtaining composite xSi3N4 - (1-x)ZrO2 ceramics. By varying the grinding conditions (grinding speed), as well as the concentration of initial components in the composition of xSi3N4 - (1-x)ZrO2 ceramics, it is possible to obtain high-strength ceramics, which have high resistance to external influences.